(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Background Hypertension is one of the most common non-communicable disease. There are a number factors, presently prevalent in our daily life that are increasing the prevalence of hypertension in nearly all age groups, but more as age increases. Beta receptor antagonists are one of the groups of drugs used in all grades of hypertension. Ca2+ channel blockers are the other class of antihypertensive agents, used in different situations of hypertension. But many times, single drug therapy is not sufficient to maintain normal blood pressure. And combination therapy has its own problems like increase side effects, cost etc. Hence, present study is undertaken to determine the difference between efficacy and tolerability of atenolol and combination of amolodopine and atenolol. Objectives To compare the efficacy and tolerability of atenolol and combination of amolodopine and atenolol in maintaining normal blood pressure. Materials and methods A total of hundred patients were taken for the study. Fifty patients are given atenolol and other fifty are given combination of amolodopine and atenolol, once a day, daily for one month. Blood pressure of all the patients is recorded daily in laying position for one month. Data collected was analyzed statistically using descriptive statistics. Any adverse effects, symptoms of hypertension and patient compliance is also noted in the follow up visits. Results Blood pressure levels were maintained at normal limits, more in combination therapy compared to atenolol alone therapy. Blood pressure variations were also less with combination therapy. Side effects were somewhat more in the combination therapy. Patient compliance was good. Interpretation and conclusion Combination of amolodipine and atenolol seems to be more effective in the treatment of hypertension in comparison to atenolol alone.